2016
DOI: 10.1097/md.0000000000005086
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Kimura disease and lupus nephritis

Abstract: Background:Kimura disease is a rare chronic inflammatory disorder with peripheral eosinophilia and elevated serum IgE and is also frequently complicated by nephropathy.Methods:We report a rare case of Kimura disease concomitant with lupus nephritis in a 72-year old male patient with recurrent unexplained lymphadenopathy, renal lesions, and immunologic abnormalities.Results:The patient was successfully managed with gamma immunoglobulin, intravenous pulse methylprednisolone therapy, hydroxychloroquine, and predn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…[ 21 ] In terms of pathological types, we found two kinds of kidney diseases: minimal change glomerulopathy and mesangial proliferative glomerulonephritis, while other types of renal diseases have been described in KD including membranous nephropathy, lupus nephritis, IgA and IgM nephropathy. [ 6 22 23 ] In this study, we found elevated serum IgE and blood basophils, and delay of the mass resection may be responsible for renal involvement. We also found that KD patients, especially those with renal involvement, often showed elevated blood CD4+ and CD8+ T cell counts and CD4+ to CD8+ T cell ratio.…”
Section: Discussionmentioning
confidence: 57%
“…[ 21 ] In terms of pathological types, we found two kinds of kidney diseases: minimal change glomerulopathy and mesangial proliferative glomerulonephritis, while other types of renal diseases have been described in KD including membranous nephropathy, lupus nephritis, IgA and IgM nephropathy. [ 6 22 23 ] In this study, we found elevated serum IgE and blood basophils, and delay of the mass resection may be responsible for renal involvement. We also found that KD patients, especially those with renal involvement, often showed elevated blood CD4+ and CD8+ T cell counts and CD4+ to CD8+ T cell ratio.…”
Section: Discussionmentioning
confidence: 57%
“…Recently the co-presence of an increasing number of autoimmune diseases with KD has been reported. Wang et al [ 5 ] reported a case of KD concomitant with lupus nephritis in a 72-year-old male patient. Ben-Chetrit et al [ 4 ] described a family in which three siblings suffered from Behcet's disease and an additional brother suffered from KD.…”
Section: Discussionmentioning
confidence: 99%
“…[ 39 ] 1 2014 Chinese Male 53 1.7 × 1.1 × 1.1 neck surgical excision no 1.01 × 10 9 / L 537.2 recurrent / 68 Hsu, S. N. [ 40 ] 1 2015 Chinese Male 33 / head, lower extremity (edema) surgical excision, PTA, Cilostazol 50 mg, Pentoxifylline 400 mg, prednisolone 1 mg/kg/day, Cetirizine 5 mg twice a day no 34 to 51% 12,400-17,200 recurrent / not clear Ye, X. [ 41 ] 1 2015 Chinese Male 47 5 in diameter cervical, subaxillary and inguinal region prednisone 0.5 mg/kg/day, thalidomide 50 mg/day no 26.11% 1081.34 recurrent tapering of prednisolone 36 Wang, H. [ 42 ] 1 2016 Chinese Male 72 / head surgical excision, Chinese herbal remedies, cetirizine hydrochloride and olmesartan 20 mg/day, gamma immunoglobulin 10 g/day for 5 days, intravenous pulse methylprednisolone therapy 500 mg for 3 days, hydroxychloroquine 0.4 g/day, prednisone 50 mg/day, a single dose of intravenous cyclophosphamide 500 mg yes 35% 149,000 recurrent / 43 Matsuo, T. [ 11 ] 1 2017 Japanese Male 42 / head surgical excision, prednisone 40 mg/day, cyclosporine 75 mg/day yes 9.40% 735 recurrent tapering of prednisolone 82 Chakraborti, C. [ ...…”
Section: Discussionmentioning
confidence: 99%